An investigation into the effect of a resin infiltrant on the micromechanical properties of hypomineralised enamel. Issue 5 (4th November 2016) - Kumar, Harleen; Palamara, Joseph Emilio Aurelio; Burrow, Michael Francis; Manton, David John
Summary: Background: Resin infiltration may alter the mechanical properties of enamel hypomineralised lesions (HL); however, variable surface layer (SL) thickness may affect resin penetration. Aims: To determine the thickness of the SL of HL and to investigate the effect of resin infiltration on the mechanical properties of HL. Design: The thickness of the SL over HL was determined using polarised light microscopy. Etching time using 15% HCl gel to remove the SL of 52 samples was determined. Selected HL and control areas of 21 teeth were infiltrated with Icon ® resin infiltrant, and cross‐sectional Knoop microhardness (KHN) measurements were recorded before and after resin infiltration. Results: Ninety‐six point five per cent of HL had a detectable SL with mean thickness of 58 ± 29 μ m. Application of HCl for 120 s produced a mean MIH erosion depth of 58 ± 12 μ m. Eleven of 21 samples had evidence of infiltration using visual examination. The infiltrant penetrated some of the HL leading to an increase in KHN (111 ± 75 KHN) which, when compared to adjacent non‐infiltrated HL (96 ± 52 KHN), was not statistically significantly different ( P = 0.56). Conclusions: There was marked variation in the SL thickness of HL. Resin infiltration of HL did not increase microhardness significantly.